A microscale-based numerical model for investigating hygro-thermo-mechanical behaviour of 3D printed concrete at elevated temperatures. (15th August 2022) - Han, Nv; Xiao, Jianzhuang; Zhang, Lihai; Peng, Yu
Highlights: Hygro-thermo-mechanical model of 3DPC at elevated temperatures is developed. Pores in 3DPC are ellipsoidal and tend to be parallel to printing direction. Failure of interlayers lead to delamination of 3DPC under elevated temperature. Abstract: The present study aims to develop a microscale-based numerical model for studying the coupled hygro-thermo-mechanical behaviour of the 3D printed concrete (3DPC) specimens at elevated temperatures. The pore structure of 3DPC and mould-cast concrete (MC) specimens were firstly reconstructed using CT scanning images and then imported into the geometry model to analyze the hygro-thermo-mechanical behaviour of both 3DPC and MC specimens. The results show that the 3DPC specimen has lower porosity, average compactness, and pore diameter than MC. The thickness of the interlayer area measured in 3DPC specimens is around 100 µm. The simulation results of elevated temperature failure forms agreed with the experimental observations. The failure of the interlayer led to the delamination of 3DPC specimens under elevated temperature, while the MC specimens were broken into several pieces due to the stress concentration around the pores.